Perbaikan Proses Bisnis Menggunakan Business Process Improvement Pada Badan Pusat Statistik Kabupaten Kediri - Claudio Canigia Guntara; Nanang Yudi Setiawan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Badan Pusat Statistik is non-department government institutions which provide data for government and society needs, whereas the Survei Sosial Ekonomi Nasional well known as Susenas was held. However, when the Sunesas program of Badan Pusat Statistik of Kediri executed, the level achievement from every process is lower than other regions in the province of East Java. Thus, based on the problems these studies are to analyzed business process Susenas Program problems and recommended the business process improvement. Then, collecting the data by interviewed and observed to know the existed business process using Business Process Model and Notation (BPMN). There are three main business processes, namely pemutakhiran blok sensus business process, pencacahan sampel rumah tangga business process, and pemeriksaan berkas business process. Then, analyze the problem using The Fault Tree Analysis (FTA) method to get the root cause of each business process. Then, improving the business process using Business Process Improvement (BPI) using Streamlining tool. From the result of the comparison between the as-is business process and the to-be business process showed that on the pemutakhiran blok sensus business process experienced an average time acceleration of 23.85%, on the pencacahan sampel rumah tangga business process experienced an average time acceleration of 47.76%, and on the pemeriksaan berkas business process experienced an average time acceleration of 8.15%.